13C CP/MAS NMR studies on the curing characteristics of phenol formaldehyde resin in the presence of nano cupric oxide and surfactants. II. Effect of CuO loading levels. Issue 3 (26th September 2014) - Gao, Wei; Du, Guanben; Kamdem, Donatien Pascal
Abstract : The effect of various loadings of nano cupric oxide (CuO) and surfactants in the formulation of phenol formaldehyde (PF) adhesive was investigated using solid 13 C CP/MAS NMR. Bonding strength and water resistance of plywood made with the modified adhesive were conducted. Solid NMR analysis showed that the addition of nano CuO alone or in combination with surfactant together was effective in improving the curing property of PF resin, which was confirmed by the NMR reveal that the amount of aliphatic carbons from methylene linkages increase with the addition of nano CuO in the PF resin. The addition of the mixture of alkane surfactant and nano CuO in the resin improved the water resistance property of the resulted plywood as well. POLYM. COMPOS., 37:949–954, 2016. © 2014 Society of Plastics Engineers